The riders come out at night : brutality, corruption, and cover-up in Oakland - Winston, Ali; BondGraham, Darwin (Atria Books, an imprint of Simon & Schuster, Inc., 2023)
"Over the last 60 years, more has been done in Oakland to reform policing than any other American city-and yet, Oakland has failed to reign in the tendencies of its police to prey upon, rather than protect, its communities. Why is this, and what does it mean both for Oakland, and for America? THE RIDERS COME OUT AT NIGHT will be the first authoritative account of the Oakland Police Department's troubling history of violence, secrecy, and mismanagement, and the city's unfulfilled promise to implement constitutional policing. By examining cases of police violence and corruption in one of America's most iconic cities, the Polk Award-winning investigative duo, Ali Winston & Darwin BondGraham, illustrate why criminal justice reform has proven an elusive goal for the entire nation. Their investigation will introduce readers to "The Riders," a band of corrupt cops running riot through the city, and to Keith Batt, a "fresh out of the academy" rookie assigned to patrol with the Riders. Winston & BondGraham deftly maneuver between the worlds of intransigent police culture to City Hall, where a lack of political will to see through reforms (and local prosecutors who failed to hold officers accountable) conspire to keep these cycles of brutality in place. Through never-before-seen reporting and interviews, the authors paint a portrait of a city-and nation-in crisis, and the steps needed to finally, once and for all, effectively address policing in the Unites States"--